Coeficientes de perda de carga em valvulas e acessorios no escoamento laminar de fluidos nao-Newtonianos - Telis-Romero, Javier [UNESP]; Gratao, Aha Carolina A [UNESP]; Garcia-Cruz, Crispin H. [UNESP]; Telis, Vania R N [UNESP] (My University, 2000)
Friction loss coefficients for laminar flow of xantan gum solutions (concentrations in the range of 0.1-0.5% by weight) through valves and fittings were experimentally determined. The rheological behavior, studied by means of a concentric cylinder rheometer, was pseudoplastic, being well described by the Ostwald-De Waele model with non-linear correlation coefficients (r) between 0.998 and 0.999. In the pressure drop measurements the following fittings were employed: completely open and half way open ball valve, completely open and half way open angle valve, tee used like coupling, tee used like a 90° elbow, short radius 90° elbow and coupling. The results showed that the friction loss coefficients increased with decreasing generalized Reynolds number. The friction loss coefficients could be well adjusted by a potential model, suggested by Kittredge & Rowley (1957) for Newtonian fluids, K f = A(Re g) -B, with correlation coefficients between 0.837 and 0.999.
Friction loss coefficients across valves and fittings for laminar flow of non-Newtonian fluids
Keywords: Correlation methods; Friction; Non Newtonian liquids; Pipe fittings; Pressure drop; Pressure measurement; Reynolds number; Rheology; Rheometers; Valves (mechanical); Concentric cylinder rheometers; Friction loss coefficients; Nonlinear correlation coefficients; Open ball valves; Xantan gum solutions; Laminar flow